Fault early warning model of 4G base station out of service based on centralized monitoring data resources - Yang WANG; Yi MAN; Zhipeng CHEN (Dianxin kexue)
4G wireless base station equipment is an important link which has direct impact on information communication network customer service quality,and 4G wireless base stations out of service fault will directly block users' normal communication.Aiming at these problems,based on the centralized monitoring warning message data resources through association rule mining and time trace deduction analysis,4G base stations out of service fault short-term warning was achieved.Based on centralized monitoring equipment performance data resources,by the classification of network elements (data cleaning,feature selection,network elements clustering),index dimension reduction (grouped by cluster,principal component analysis),principal component expression and out of service fault correlation analysis,performance indicators selection and threshold analysis,4G base stations out of service fault long-term warning was achieved.The test can accurately predict the 27.8% of 4G base station equipment out of service fault next month.